2015
DOI: 10.11113/jt.v77.6910
|View full text |Cite
|
Sign up to set email alerts
|

Soft Lean Practices for Successful Lean Production System Implementation in Malaysia Automotive Smes: A Proposed Framework

Abstract: Challenging and competitive business environment has prompted the automotive industry to restructure its manufacturing practices. Nowadays, Lean Manufacturing (LM) has been widely implemented in the automotive industry. LM supported the manufacturing companies, particularly automotive manufacturers in becoming world class manufacturers through various lean practices. However, lean implementation faced various obstacles such as the lack of management commitment and support, the absence of organizational communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 95 publications
0
24
0
Order By: Relevance
“…LM has also been studied in the small and medium-sized enterprise (SME) environment. Several authors have conducted research on LM in SMEs, such as critical success factors (CSFs) [5,7,8]; enablers and inhibitors [6,10]; frameworks, road maps, and methodologies [11][12][13][14][15][16][17]; and LM implementation in SMEs [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…LM has also been studied in the small and medium-sized enterprise (SME) environment. Several authors have conducted research on LM in SMEs, such as critical success factors (CSFs) [5,7,8]; enablers and inhibitors [6,10]; frameworks, road maps, and methodologies [11][12][13][14][15][16][17]; and LM implementation in SMEs [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, out of ten definitions compilation, only one definition was proposed by local (Malaysian) authors (Abdul Wahab et al, 2017). Although, there were also other local authors had used the term "Lean Production" in their study, they did not offer their own definition to operationalized this strategy (Anvari et al, 2011;Che Mamat et al, 2015;Iteng, Abdul Rahim, & Ahmad, 2017;Puvanasvaran et al, 2008). Therefore, this review supports Abdul Wahab et al (2017) qualitative finding that claimed "Lean Production" term was more popular among American scholars and practitioners.…”
Section: Literature Review Lean Production Lean Manufacturing or Leamentioning
confidence: 52%
“…Apparently, various terms used to refer lean application in manufacturing environment in the literatures remained a problem for researchers and practitioners to properly understand lean and by extension to successfully implement it (Abdul Wahab, Mukhtar, & Sulaiman, 2017;Gurumurthy & Kodali, 2009;Islam, Sorooshian, Rahamaddulla, & Mustafa, 2018;Mirdad & Eseonu, 2015). In fact, many literatures simply used these terms (especially LP or LM) interchangeably without in-depth explanation on why these terms were regarded the same (Anvari, Ismail, & Hojjati, 2011;Bandehnezhad, Zailani, & Fernando, 2012;Che Mamat, Md Deros, Ab Rahman, Omar, & Abdullah, 2015;Muslimen, Mohd Yusof, & Zainal Abidin, 2011;Puvanasvaran et al, 2008;Shah & Ward, 2003). Therefore, this article aimed to make detailed comparisons between these terms in the hope of providing scholars and practitioners with clear insights regarding lean application in manufacturing environment.…”
Section: Introductionmentioning
confidence: 99%
“…The era of mass production came to a halt in 1980s and was duly replaced by agile or flexible production, which marked the beginnings of revolution in industrial management (Duguay et al, 1997). This led to the conclusion that lean manufacturing enables industries to walk towards a path of business excellence (Mamat et al, 2015;Mejabi, 2003). Koskela (1992) indicated that the major categorization of lean philosophy can be done by segregating the processes in production systems to conversion activities and flow activities, the former being value adding and the latter being time and consuming, while adding no value to the product.…”
Section: Lean Manufacturingmentioning
confidence: 99%